Development process improvement of a game development company - Gadi, Peter Paul A. (Quezon City University of the Philippines Diliman, 2008)
The aim of this project paper is to implement and document process improvement steps undertaken in a game development company. The game development company under study is Anino Games [1], a local game development company of which the author is a shareholder. The author has proposed a DMAIC project to document and improve the game development processes of the said company as the basis of the TM 299.2 paper. Initially, the paper was targeted to merely document the development processes that Anino used that fell under the scope of Agile Game Development [3]. The project has changed during project progress to process improvement. The scope of the paper is to make use of the DMAIC framework, Six Sigma references and Agile Game Development practices in order to ensure that all project deadlines are met. Based on readings on process improvement and the availability of resources, The DMAIC process was chosen as a framework for the project paper. By choosing this framework, the project progressed through several phases of documentation and implementation, at times moving back and forth through the DMAIC phases. At the Define Phase, company documents as well as several game development methodology references were used to understand the company's current processes. Process maps and a SIPOC diagram were created during this phase. Also, the company knowledgebase (which is captured in the company's Trac databases) as well as client contracts were evaluated to determine the Voice of the Customer, to ensure that the proposed project will be attuned to customer needs. Lastly, the Project Charter was created during this phase. At the Measure Phase, data from measurements recorded in the company's internal databases that were related to project delays were extracted. These measurements were then mapped into Pareto Charts and graphs so that they could be visualized more effectively for the next phase.
The next phase is the Analysis Phase. During this phase, a Cause and Effect Analysis was done based on the measured data. Several Causal Hypothesis Statements [11] were then inferred based on the visualized data. Several of these hypothesis statements were then selected as candidates to address for the next phase. These hypothesis statements were then matched with respective solution statements, along with the creation of an improvement plan. These were also be used for the next phase. The Improvement Plan is then implemented during the Improvement Phase. Several action items were defined, each of were done in the succeeding projects. The project paper is then used as documentation for the benefits that were gained from each of the improvement steps, along with any of the impediments that were faced during their implementation. Lastly, during the Control Phase, a Control plan is then drafted that lists the action items that need to be addressed in order to ensure that the benefits that were achieved by the Improvement steps are maintained. Some of the items in the Control Plan still haven't been implemented, and these are listed as part of the Further Action Steps to be taken. The DMAIC process improvement project was a helpful exercise to the game development company, as it has allowed those involved in process definition to make use of Six-Sigma literature supported ideas and tools in implementing any process improvements. Though some of the benefits that would be gained by the implementation of the steps in the Improvement Plan are yet to be fully realized, the benefits are evident based on developer team interviews. Moving forward, the company could be able to build on any improvements from this project by following the actions in the Further Action Steps. Listed at the end of the paper are also some Lessons Learned regarding the implementation of the project. These can serve as a guideline for Anino to further continue its process improvement plans.
In partial fulfillment of the requirements in TM 299.2
Thesis
Includes bibliographical references
Keywords: Games; Game development project